Recent Progress in 808 nm Excited Upconversion Nanomaterials as Multifunctional Nanoprobes for Visualized Theranostics in Cancers - Zeng, Leyong; Wu, Di; Tian, Ying; Pan, Yuanwei; Wu, Aiguo; Zhang, Jinchao; Lu, Guangming (Current Medicinal Chemistry, 2018)
Near-infrared (NIR) light responsive nanomaterials have attracted considerable attention due to their location in the biological window. Especially, lanthanide-doped nanomaterials exhibit unique upconversion luminescence (UCL) properties with low background interference and long luminescence lifetime, which makes them promising in imaging diagnosis of cancers. Compared with traditional upconversion nanomaterials excited by 980 nm laser, 808 nm excitation can overcome the disadvantages of high heating effect and weak penetration depth induced by excitation source. Therefore, developing 808 nm excited upconversion nanoprobes will be important for the in vivo bio-imaging and visualized theranostics of tumors in deep-tissue. In the review paper, we systematically summarized the synthesis strategy and luminescence modulation of Nd3+-sensitized upconversion nanomaterials under 808 nm excitation, discussed the influence of excitation source on heating effect and penetration depth, and particularly focused on their applications in UCL imaging, multi-modal imaging and imaging-guided therapy of cancers.
Keywords: Nd3+-sensitized upconversion nanomaterials